2018
DOI: 10.1073/pnas.1808412115
|View full text |Cite
|
Sign up to set email alerts
|

Piano training enhances the neural processing of pitch and improves speech perception in Mandarin-speaking children

Abstract: Musical training confers advantages in speech-sound processing, which could play an important role in early childhood education. To understand the mechanisms of this effect, we used event-related potential and behavioral measures in a longitudinal design. Seventy-four Mandarin-speaking children aged 4-5 y old were pseudorandomly assigned to piano training, reading training, or a no-contact control group. Six months of piano training improved behavioral auditory word discrimination in general as well as word di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 55 publications
5
91
2
4
Order By: Relevance
“…It is doubtful that functional changes occurring after a musictraining intervention represent domain-general improvements in cognitive function. Instead, it is probable that such neural patterns underlie the enhancement of musicrelated skills such as pitch discrimination (e.g., Nan et al, 2018). It is thus imperative not to erroneously interpret -as sometimes happens (e.g., Habibi et al, 2016) -that functional neural changes in brain areas involved in domaingeneral cognitive abilities are evidence of cognitive enhancement.…”
Section: Triangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is doubtful that functional changes occurring after a musictraining intervention represent domain-general improvements in cognitive function. Instead, it is probable that such neural patterns underlie the enhancement of musicrelated skills such as pitch discrimination (e.g., Nan et al, 2018). It is thus imperative not to erroneously interpret -as sometimes happens (e.g., Habibi et al, 2016) -that functional neural changes in brain areas involved in domaingeneral cognitive abilities are evidence of cognitive enhancement.…”
Section: Triangulationmentioning
confidence: 99%
“…Rather, the purpose of this article has been to clarify what are the real effects of music training in order to allow people to make informed decisions. Educators and policymakers should be aware that music training provides no benefits on non-music-related cognitive or academic skills (e.g., Nan et al, 2018). As far as we are concerned, even in the absence of other cognitive or academic benefits, it is worthwhile learning an art present in nearly all the cultures in human history.…”
Section: Recommendations For Future Research and Conclusionmentioning
confidence: 99%
“…Metaanalysis confirms that positive effects of music training are more likely to emerge from studies with such suboptimal (rather than optimal) designs (8). Mankel and Bidelman (1) also cite short-term, intensive interventions that are unlike real-world music lessons (e.g., no practicing at home) and provide no evidence for long-term effects (9). In short, previous evidence of plasticity is suggestive at best.…”
mentioning
confidence: 99%
“…Researchers in this field have reached inconsistent conclusions. While most of them have expressed optimism about the benefits of music training (e.g., Barbaroux, Dittinger, & Besson, 2019;Nan et al, 2018;Tierney, Krizman, & Kraus, 2015), others have found this enthusiasm unjustified (e.g., Kempert et al, 2016;Rickard, Bambrick, & Gill, 2012). Like in many other fields in the social sciences, meta-analyses have been carried out to resolve such controversies.…”
Section: Experimental Evidencementioning
confidence: 99%